Real exchange rates and the long-run effects of aggregate demand in economies with underemployment - Peter Skott; Martin Rapetti; Arslan Razmi (University of Massachusetts, Department of Economics, 2012)
Successful economic development to a large extent derives from the mobilization of underemployed resources. Demand policy can play an important role. It is critical, however, to consider balance of payments constraints and to ensure an expansion of investment in the modern sector. A combination of investment promotion and exchange rate intervention may be required to achieve these goals.
Keywords: F43; O11; O41; 330; exchange rate; balance of payments; economic growth; inflation; aggregate demand; two-sector model